Representasi feminisme dalam series The Queen’s Gambit: Lebih dari sekedar catur - Salsabila, Hanum - (Maliki Interdisciplinary Journal, 2025)
This article examines the representation of feminism in Scott Frank’s series The Queen’s Gambit, focusing on the main character, Beth Harmon. The central issue addressed is how feminism, particularly liberal feminism, is portrayed through Beth’s journey in the male-dominated chess world. Employing a feminist analytical approach, the research highlights aspects of gender representation, equality, and critique of patriarchy. The findings reveal that Beth embodies liberal feminism by emphasizing independence, rationality, and individual achievement as resistance to patriarchal norms. She demonstrates that women possess intellectual abilities equal to men, even in masculine domains such as chess. Furthermore, the series uncovers the social challenges faced by successful women, including stigma, prejudice, and societal suspicion. Thus, The Queen’s Gambit serves not only as entertainment but also as a critique of patriarchal structures and a reflection on the importance of gender equality. In conclusion, the series illustrates that gender equality can be realized through the recognition of women’s individual capacities, social support, and the deconstruction of patriarchal values that restrict women’s potential.